The Social Ecology of Resolving Family Conflict Among West African Immigrants in New York: A Grounded Theory Approach. Issue 1 (2nd July 2013) - Rasmussen, Andrew; Chu, Tracy; Akinsulure-Smith, Adeyinka M.; Keatley, Eva
Abstract: The current study employs a grounded theory approach to examine West African immigrants' resolution of parent–child conflict and intimate partner conflict. Data from 59 participants present an interactive social ecological framework, where a lack of resolution at one level results in attempts to resolve problems at higher levels. Four levels are identified within West African immigrants' problem solving ecology, each with specific actors in positions of authority: individual/dyadic (parents and spouses), extended family (which includes distant relatives and relatives living in home countries), community leadership (non‐family elders and religious leaders), and state authorities. From participants' descriptions of family challenges emerged a picture of a social ecology in flux, with traditional, socially conservative modes of resolving family conflict transposed across migration into the more liberal and state‐oriented familial context of the United States. This transposition results in a loss spiral for the traditional social ecology, differentially affecting individual actors within families. Implications for helping professionals working with new immigrant communities include identifying variability in openness to adapting structures that are not working well (e.g., patriarchal protection of abusive husbands) and supporting structures known to be associated with well being (e.g., collective monitoring of youth).